'Unsung Heroines': Celebrating the care provided by grandmothers for children with parents in prison. (September 2016) - Raikes, Ben
This article focusses on the issues that arise when grandmothers are put in the position of caring for their grandchildren while their parents are in prison. It will present the lived experience of three grandmothers who are in this position and 16 imprisoned mothers, whose mothers were caring for their children, who participated in two focus groups at two different female prisons. It is now well established that parental imprisonment generally has a negative impact upon children. Children with imprisoned mothers often face the most disruption to their lives. Many children with mothers in prison are cared for by their grandparents, with grandmothers generally doing the majority of the care. Pressures faced by grandparent carers of children with incarcerated parents occur as a result of stigma, loss, isolation, poor health and a lack of practical, emotional and financial support. If grandparents were not willing to provide this care, many more children with parents in prison would face being placed in foster care, or in children's homes. The complexities encountered by both grandparents and imprisoned mothers as a result of the changes in roles that arise from these circumstances will be explored.